The Cognitive Style Inventory, Reading Habit, and Reading Achievement Among Undergraduate EFL Students - Ariyani, Hastin Yoka; Budiyanto, Darmawan; Manurung, Jenny Elvinna (Journal of English Education, 2024)
Reading requires the ability to detect and evaluate words inside sentences, as well as extract underlying information. This research focused on finding out whether or not there was any significant correlation among cognitive style inventory, reading habit and reading achievement of undergraduate EFL students at Tridinanti University. This study used quantitative design with correlational approach and involved 65 students as the sample through total sampling. The data were collected by using cognitive style inventory questionnaire, a reading habit questionnaire, and a reading achievement test. The data were analyzed by using Rank-Spearmen to investigate the correlation among cognitive style inventory, reading habits and reading achievement. After analyzing and calculating the data, it was found that there was significant correlation among cognitive style inventory, reading habits and reading achievement of undergraduate EFL students at Tridinanti University, since the p-value (0,301) was higher than r-table (0,244). It means that, Ho (null hypothesis) was rejected and Ha (alternative hypothesis) was accepted. The degree of correlation coefficients was weak category.